Drama DRAMA MUSIKAL: PETER AND THE WOL Karya Sergie Prokofiev,Op.67, Sebagai Bentuk Orchestrasi Dongeng: Pendahuluan - Tatang Rusmana (GETER : Jurnal Seni Drama, Tari dan Musik, 2022)
Peter And The Wolf (A Symphonic tale for Children) by Sergei Prokofiev, Op. 67, written by Prokofiev in 1936. The performance of this tale is like a monologue drama. It is rare to find a tale performance or a monologue drama that is composed with music in an ensemble. The narrator tells a children's story, while the orchestra illustrates it using different instruments to play a "theme" representing each character. This work of Prokofiev is one of the works that is often featured throughout the classical repertoire. The storyline is kind of like a Prokofiev biography, depicting Russians living in forest areas. In their cosmic view, the theme "Peter catches the wolf" has the meaning of "man's victory tames Nature". In addition to messages of kindness about vigilance, courage, and resourcefulness, there are also images of the stubborn old Soviet generation (grandfather) and the message of the victory of Man (Peter) in taming Nature (Wolf). Peter and The Wolf are well written score. The interesting thing, it is written in the form of a symphony orchestra, besides having an epic storyline in the spectacle of heroic stories. The theory used from the analysis process to the performance is (deep structures) Richard Schechner in three stages of work, namely: 1). Preparation, 2). Performances, 3). Aftermath. The purpose of research and performance is to find concretization of receptions and concretization of dramaturgy. When the performance transformation is carried out in an Indonesian-language presentation, it is hoped that it will be able to provide semiotic novelty to the target culture for an explanation of the development of Indonesian musical dramas.